Pengembangan Media E-Booklet Pembelajaran Berbasis Flipbook Maker pada Materi Identifikasi Karir Siswa - Syifa Dwi Hendrianti; Sholeh Hidayat; Suherman Suherman (UNDIKMA, 2021)
The purpose of this study was to develop an e-booklet media based on flipbook maker on career identification material for class XI students at SMKS YP 17 Cilegon. The method used is the R&D method. This development research uses the steps developed by Borg & Gall. There are three subjects in this study, namely material experts, media experts, and 30 students of class XI Marketing Department of Marketing. The instrument used is a validation sheet that is tested on media experts, material experts, and student responses. Based on the results of research that has been carried out at SMKS YP 17 Cilegon, it can be concluded that the development of flipbook maker-based e-booklet media has an average value of 89.28% which is categorized as very feasible with details of the percentage of media experts of 90.6%, material experts of 93.7%, and student responses of 83.56% so that the media is included in the appropriate category.